Apoptotic PET Imaging of Rat Pulmonary Fibrosis With [F]ML-8 - Ying Xiong MM; Dahong Nie BM; Shaoyu Liu PhD; Hui Ma BM; Shu Su BM; Aixia Sun PhD; Jing Zhao MD, PhD; Zhanwen Zhang PhD; Xianhong Xiang MD, PhD; Ganghua Tang MD, PhD (Molecular Imaging)
Objective: To investigate the value of 2-(3-[ 18 F]fluoropropyl)-2-methyl-malonic acid ([ 18 F]ML-8) positron emission tomography (PET) imaging of rat pulmonary fibrosis. Methods: Male Sprague-Dawley rats were divided into 2 groups, including pulmonary fibrosis model group and control group. The rat model was established by an intratracheal instillation of bleomycin (BLM). Control rats were treated with saline. Positron emission tomography/computed tomography (CT) with [ 18 F]ML-8 or 18 F-fluorodeoxyglucose ([ 18 F]FDG) was performed on 2 groups. After PET/CT imaging, lung tissues were collected for histologic examination. Data were analyzed and comparisons between 2 groups were performed using Student t test. Results: Bleomycin-treated rats showed a higher lung uptake of [ 18 F]ML-8 than control rats ( P < .05). In BLM-treated rats, the lung to muscle relative uptake ratio of [ 18 F]ML-8 was also higher than that of [ 18 F]FDG ( P < .05). Pathological examination showed overproliferation of fibroblasts and deposition of collagen in lungs from BLM-treated rats. Compared to control rats, BLM-treated rats had higher lung hydroxyproline content ( P < .05). Immunofluorescence staining indicated more apoptotic cells in BLM-treated rats than those in control rats. Moreover, the apoptosis rate of lung tissues obtained from BLM-treated rats was higher than that from control rats ( P < .05). Conclusions: 2-(3-[ 18 F]fluoropropyl)-2-methyl-malonic acid PET/CT could be used for noninvasive diagnosis of pulmonary fibrosis in a rat model.